Assessment of Digital Banking Attributes and Customer Satisfaction in the Nepalese Banking Sector - Tamang, Govinda; Bhattarai, Nisha; Shakya, Subarna (SOMTU Journal of Business and Management Research, 2025)
Over time, the digitalization of banking operations has accelerated, aligning with Nepal’s broader digitization framework and regulatory efforts led by Nepal Rastra Bank (NRB). This study assesses key digital banking attributes and customer satisfaction in Nepal’s commercial banking sector. Using a structured questionnaire, data were collected from 450 customers working in the IT sector who actively use digital banking services. Findings reveal that perceived credibility and convenience are the most influential factors shaping digital banking services in Nepal, both demonstrating strong statistical significance. Although perceived ease of use showed a positive influence, it was not statistically significant, while perceived usefulness was only marginally significant. These results suggest that while usability and functionality are important, trust and convenience play a more critical role in shaping user satisfaction and loyalty. The study offers important implications for banks, digital service developers, and policymakers. By enhancing platform credibility, improving security, and expanding convenient features, stakeholders can better align with customer expectations and foster sustained engagement in Nepal and underscores the value of customer-centric approaches in driving digital transformation within the financial sector.